The Relationship Between Per Capita GDP and Road Accidents in Sri Lanka: An ARDL Bound Test Approach - Bhavan, T (Asian Journal of Empirical Research, 2018)
The objective of this study is to examine the relationship between road accidents and per capita GDP in Sri Lanka during the period of 1977 to 2016. The study examines the existence of Kuznets curve relationship between number of road accidents and per capita GDP in Sri Lanka, and the relationship of some other variables such as merchandise imports from various regions and different age group of population as well. The Auto Regressive Distributed Lags (ARDL) bound test approach is employed to analyse the time series data. The findings of this study confirm the existence of the Kuznets curve relationship between road accidents and per capita GDP. The results further reveal that there is a long-run relationship between road accidents and merchandise imports from high income and East Asian countries, urban population and age group of population 30-34 and 35-39. Coefficients of these variables are statistically significant at 1% level and positively associated with number of accidents in Sri Lanka.